Pivotal role of plasminogen-activator inhibitor 1 in vascular disease - (:unkn) unknown (WILEY, 2005)
Fibrinolysis plays a crucial role in the development of vascular disease. The interface between the plasminogen activators and inhibitors determines the fibrinolytic potential of human blood. In addition to fibrin degradation, fibrinolytic system components modulate several complex biological events such as angiogenesis, tumorigenesis, arteriosclerosis and cellular migration. Recent experimental and clinical data indicated that PAI-1 as a novel vascular risk factor. In this concise review, we will examine the accumulating evidence suggesting that there is an intricate relationship between these systems which may provide new therapeutic strategies for prevention of vascular disease. (C) 2005 Blackwell Publishing Ltd.
Keywords: plasminogen-activator inhibitor 1; atherosclerosis; thrombosis; RENIN-ANGIOTENSIN SYSTEM; FAST-ACTING INHIBITOR; ENDOTHELIAL-CELLS; RAPID INHIBITOR; HEPATOMA-CELLS; HUMAN-PLASMA; IN-VITRO; PAI-1; GENE; PURIFICATION